The Age Limit for Presidential and Vice-Presidential Candidates in Constitutional Court: An Implication of Ethical Sanctions for Judges - Muhammad Fauzan; Dewi Iriani; Arief Budiono; Mahesa Rannie; Elsa Sintya Marvinda (Jurnal Dinamika Hukum, 2024)
Almas filed a lawsuit to lower the minimum age requirement for presidential and vice-presidential candidates from 40 to 35 years, arguing that the existing rule contradicts the 1945 Constitution. This lawsuit sparked debate but also created opportunities for young and talented candidates to run for office. The Constitutional Court partially granted the lawsuit through Decision No. 90/PUU-XXI/2023, maintaining the minimum age at 40 but allowing exceptions for those with experience as regional heads. This ruling was controversial as it introduced a new legal interpretation within Indonesia’s constitutional system. This study aims to analyze how Constitutional Court judges interpret the age requirement for presidential and vice-presidential candidates and how the court’s final authority in this decision has become a subject of controversy. The research employs a jurisprudential approach, examining court decisions as primary data and supplementing them with secondary data from literature reviews, the 1945 Constitution, and the Election Law (2017). Findings indicate that Decision No. 90/PUU-XXI/2023 remains controversial as it is perceived to be inconsistent with constitutional and democratic principles. Additionally, several Constitutional Court judges were sanctioned by the Court’s Honorary Council for ethical violations, further fueling the debate surrounding this ruling. Despite the controversy, the decision remains final and binding, while also opening opportunities for younger leaders with prior leadership experience to run for president or vice president before reaching the age of 40.